Floristic and coenotic descriptions of plant communities of artificial forest planting in southern Kryvyi Rih area (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The paper presents comparative analysis of floristic and coenotic descriptions of even-age (50 years old) plant communities with different specific compositions in Southern Kryvyi Rih area. We carried out their taxonomical and biomorphological descriptions; regularities of quantitative distribution of species according to their phytocoenotical activitity and occurence are ascertained. We ascertained that vegetation of these artificial plantings is characterized by low specific richness: 38–40 species, but species quantity of pine forests on sands consists 90 species. We ascertained that correlation of species according their occurence and phytocoenotical activity depends on kind composition of plantings determining their light structure type.
Keywords: artificial forest planting, floristic and coenotic descriptions, Southern Kryvyi Rih area.